Pengaruh Struktur Modal Terhadap Kinerja Perusahaan Dengan Keputusan Investasi Sebagai Variabel Mediasi - Devina Himelda, Elsa Imelda (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this research is to empirically examine the influence of capital structure measured by Total Debt Ratio (TDR) toward firm performance measured by Tobin’s Q with investment decision measured by Market to Book Asset Ratio (M/BAR) as mediating variable. This study uses secondary data obtained from the Indonesia Stock Exchange official website. The population of this study is the banking companies listed on the Indonesia Stock Exchange for the period of 2016-2018. Based on several criteria, 42 banking companies listed on the Indonesia Stock Exchange are selected as samples in this study. This samples are determined using purposive sampling method. The method of analysis was multiple linear regression using EViews 10 program. Sobel Test is used to test the significance of mediating effect. The results of this study indicate that capital structure has a negative and significant effect on firm performance, while investment decisions have a positive and significant effect on firm performance. Investment decisions are able to mediate the effect of capital structure on firm performance.